Evaluation Of End-To-End Anastomotic Urethroplasty In Patients With Post-Traumatic Posterior Urethral Strictures - Khan, Irshad; Sabir khan , Haroon; Haider, Yazdan; Hadi, Mujtaba; Quresh, Asad Atta; Munwar (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the success rate and postoperative complications of end-to-end anastomotic urethroplasty (EEUP) in patients with post-traumatic posterior urethral stricture. Study Design: Prospective observational study. Place and Duration of Study: Department of Urology, Armed Forces Institute of Urology, Rawalpindi, over six months, from 1 October 2025 to 31 March 2026. Methodology: Forty-seven patients aged 18-60 years with confirmed post-traumatic posterior urethral stricture were enrolled by consecutive non-probability sampling. Patients with neurogenic bladder, bladder diverticulae, benign prostatic enlargement causing bladder outlet obstruction, active perineal disease or refusal to participate were excluded. All patients underwent EEUP. Surgical success and postoperative complications were assessed clinically and radiologically/endoscopically according to the departmental protocol. Data were analyzed using IBM Statistical Package for the Social Sciences (SPSS) version 25. Results: The mean age was 35.2±10.1 years. Most patients were male, 45 (95.7%), and road traffic accident was the most common cause, 30 (63.8%). EEUP was successful in 41 (87.2%) patients, while failure occurred in 6 (12.8%). Postoperative complications were recorded in 10 (21.3%) patients, including wound infection in 4 (8.5%), bleeding in 3 (6.4%) and recurrent stricture in 3 (6.4%). No statistically significant association was found between surgical outcome and age group, etiology, profession or residence (p>0.05). Conclusion: EEUP showed a high early success rate and acceptable complication profile in post-traumatic posterior urethral stricture. It remains a safe and effective reconstructive option when patients are selected and followed systematically.